PENGEMBANGAN MEDIA PEMBELAJARAN DOMINO MINUS DAN PLUS BERBASIS IT MATERI OPERASI HITUNG BILANGAN BULAT PESERTA DIDIK KELAS IV SEKOLAH DASAR - Nurmayani Nurmayani; Geovani Sembiring Meliala (Jurnal Guru Kita PGSD, 2022)
Abstract : Development of Domino Minus and Plus Learning Media Based on It Operation Material Counting Integers Grade IV Elementary School Students. The problems in this study are the lack of use of learning media in the teaching and learning process, the lack of teacher skills in making IT-based learning media, the learning methods used in the learning process are still conventional, the students' mathematics learning outcomes in the arithmetic operations material of integer addition and subtraction are still is low. The purpose of this research is to develop learning media for IT-based domino Minus and Plus Media Operations Material for Counting Integers in the mathematics learning process so that student learning outcomes increase, especially in learning mathematics in the material for counting operations on integers, adding and subtracting for grade IV Elementary School. The type of research used is research and development (Research and Development) with the Borg and Gall model which consists of 10 stages, but in this study the researchers only reached stage 7, namely: 1). Potential and Problems, 2). Data Collection, 3). Product Design, 4). Design Validation, 5). Design Revision, 6). Product Trial, 7). Product Revision. Data collection techniques are interviews, questionnaires, tests, and documentation. Qualitative and quantitative data analysis techniques. The research subjects were the fourth grade students of SDN 050616 Tanjung Karo as many as 24 students. The results of this study show that the effectiveness of the IT-Based Domino Minus and Plus learning media can be seen from the results of the pretest, namely students who complete as many as 33.33% or only 8 students whose scores are above KKM 70 while students who are incomplete or below KKM 70 are 66.67% or 16 students. The results of the posttest were 83.3% of students who completed or 20 students with scores above KKM 70 while students who did not complete or below KKM 70 were 16.7% or 4 students. From the results of the pretest and posttest showed an increase in student learning outcomes seen from the number of students who completed as many as 83.3% or 20 students. Based on these results, it can be concluded that the use of IT-based Domino Minus and Plus media in learning is feasible and effective in improving student learning outcomes.Keywords: Development Research, IT-Based Domino Minus and Plus Media, Integer Counting Operations, Student Learning Outcomes.